Contribution to the extensification/intensification debate: new trends in the Portuguese montado (Landscape and Urban Planning, 1999)
The montado is the agro-silvo pastoral system speci®c to the region of Alentejo, Southern Portugal, comprising an open formation of cork and holm oaks in varying densities, combined with a rotation of crops/fallow/pastures. Case studies in different areas of Alentejo, combining the land use and the farmers' decision making, have shown recent extensi®cation in different sub-types of montado. The agro-silvo pastoral system is in transition towards a silvo-pastoral or even purely forestry system. Cultivation is becoming less important in the system rotation, whereas livestock production is becoming more relevant and the ground cover is used only as pasture. The cork is still valuable and, in most cases, is the ®rst priority in the exploitation. New alternative uses are arising; they include hunting and rural tourism, both intended to support the preservation of the traditional landscapes. All these uses are supported directly or indirectly by the EU's CAP; for example, through agro-environmental measures. Although scrub patches are becoming larger, complete land abandonment is rare. These land use systems are based on a use that is even more extensive. Consequently the landscape is changing, but a new equilibrium, displaying new land cover mosaics, might be attained. Concomitantly, intensi®cation is occurring in certain areas. It causes degradation as a result of various management factors: (a) harvesting activity and deep ploughing in the areas where crops are cultivated, (b) too high stocking rates in relation to the carrying capacity of the system, impeding, for example, the natural regeneration of the tree cover; (c) introduction of heavy cattle breeds, which aggravates the problem of overstocking and results in direct damage to the soil structure and to the tree root system. The clearing of the shrub layer with heavy machinery affects the Quercus regeneration in both extensively and intensively managed patches, but no effective alternatives have yet been found. Today, the main landscape problem of the montado is not the abandonment of the system due to extensi®cation, but is rather: (1) whether the current extensi®cation is leading to a new equilibrium in an extensive silvo-pastoral or merely forestry system, and what type of landscape mosaic this change is creating; and (2) whether it is possible to avoid short-term intensi®cation and improve mechanisation to clear shrubs without degradation; (3) to what extent these changes depend on the CAP and how they will react to CAP changes in the future.